Muallafah Muslimat NU Buleleng Bali Religious Tolerance and Moderation in a Hindu Society in Bali - Nurlaili H., Musfiroh; Nilamsari, Wati; Shodiq, Muhammad; Roup, Mu'min; Nisa, Mauidlotun (Jurnal Penelitian Agama Hindu, 2025)
Religious conversions made by Balinese people from Hinduism to Islam or to Islam are evidence of religious moderation in Hinduism. The interaction between the Hindu community of Buleleng and the Muslim community has created a new culture or cultural acculturation and even marriage which has an impact on religious conversion from Hinduism to Islam. This article aims to reveal the tolerance and moderation of Hinduism that has a major impact on the moderate social religious activities of Muslimat NU Buleleng so that a moderate Muallafah emerges. This research is a qualitative research with Anthropology and Sociology of Religion approach. The primary data of this research are Muallafah and Muslimat NU Ranting Seririt Organisation, Buleleng District, Bali. The findings of this research are that the majority of Buleleng Bali Muallafahs come from Hinduism and make religious conversions due to marriage. The Muallafah joined the Muslimat NU because the tolerance and moderation of the Hindu community towards minority Muslims is quite high. Muslimat NU's social religious activities include Friday blessings; Pengajian Umum, Dzikir Akbar, and Reciting Burdah Covid 19 Prevention Social Service and Soft Skill Training and Economic Empowerment. The success of socio-religious activities carried out by Muslimat NU in Bali towards the majority Hindu Balinese community is evidence of tolerance and religious moderation of Hindu society in Bali so that Muallafah Muslimat NU Buleleng Bali feels living in harmony and peace without discrimination and pressure from the surrounding community and even family for choosing Islam as a new religion.